Transplacental sirolimus: a new treatment strategy for life-threatening fetal cardiac rhabdomyomas—a case report - Kaname Uno; Yoji Nomura; Masahiro Kawaguchi; Anna Ebina; Rina Imanishi; Satoru Kawai; Hiromi Hayakawa (Orphanet Journal of Rare Diseases)
Abstract Large cardiac rhabdomyomas can disturb hemodynamic flow. Tuberous sclerosis complex is the most common cause of cardiac rhabdomyoma in fetuses. Recently, a mammalian target of rapamycin (mTOR) inhibitor effectively treated rhabdomyomas associated with tuberous sclerosis. Here, we report the effectiveness of an mTOR inhibitor in treating a fetus with large rhabdomyomas exhibiting severe heart failure when administered transplacentally. A 30-year-old pregnant woman was transferred to our hospital due to the presence of a cardiac tumor in the left ventricle (LV) of the fetus, which gradually enlarged to > 40 mm in diameter. The diastolic and systolic functions of the LV were completely disrupted. At 32 weeks of gestation, the fetus showed severe heart failure (cardiovascular profile score 7), with a high risk of death. The hemodynamic flow was consistent with hypoplastic left heart syndrome. Fetal magnetic resonance imaging revealed several cranial regions with 7.9 × 6.9 mm subependymal giant cell astrocytoma (SEGA). The fetus was clinically diagnosed with tuberous sclerosis, and therapy was initiated with maternally administered sirolimus, an mTOR inhibitor. Sirolimus effectively reduced the size of the tumor and improved the hemodynamics of the fetus. No severe complications occurred in the mother or fetus. The baby was born at 39 weeks of gestation with a mildly reduced LV ejection fraction. In addition, the dimensions of the intracranial SEGA decreased somewhat following initiation of maternal sirolimus treatment. Postnatal genetic testing confirmed a mutation in the TSC2 gene. Currently, the baby is 3 months old with normal neurological development. Transplacental sirolimus administration can be a useful in treating large rhabdomyomas that disturb fetal hemodynamics.